Modelos de negocios de los emprendimientos periodísticos con mayor reconocimiento de la provincia de El Oro - Espinoza Arias, Estephany Mishelle (Machala, 2020)
The following degree work shows the analysis of the digital journalistic undertakings in the province of El Oro, created by amateurs and communication professionals, in order to create content and information for the Orense community and social network users, in addition to identifying business models that apply in digital media. Through case analysis, we identified journalistic enterprises positioned and recognized in the digital world, this due to the age (longer time in the market), evolution of the medium, variety of content, number of "I like", followers and recommended in the social network Facebook. This taking into account the criteria of professionals in this area, which allowed the selection of the sample. The profiles and Fanpage on Facebook were secretly analyzed, and in order to have a context of the operation of each of the digital media, -considered enterprise-, interviews were conducted with communication professionals, specialists in the digital area and founders of journalistic media, knowing the business model to maintain and make their companies profitable. The results of this research are presented in tables, arranging the answers of the interviews, proceeding to interpret them, evidencing through statistical graphs, the information obtained from each digital media, to then show the conclusions and recommendations of the research work. With this research, it was possible to establish the most recognized digital media in the province of El Oro, which were subjected to a thorough analysis, also determined the factors that have allowed the positioning in the market of El Oro.
El siguiente trabajo de titulación muestra el análisis de los emprendimientos periodísticos digitales de la provincia de El Oro, creado por aficionados y profesionales de la comunicación, con el fin de crear contenido e información para la comunidad orense y usuarios de redes sociales, además se identificaron modelos de negocios que aplican en medios digitales. Mediante el análisis de caso, se identificaron los emprendimientos periodísticos posicionados y reconocidos en el mundo digital, esto debido a la antigüedad (mayor tiempo en el mercado), evolución del medio, variedad de contenido, número de “me gusta”, seguidores y recomendados en la red social Facebook. Esto tomando en cuenta los criterios de profesionales de esta área, que permitió seleccionar la muestra. Los perfiles y Fanpage en Facebook fueron analizados sigilosamente, y para tener un contexto del funcionamiento de cada uno de los medios digitales, -considerados emprendimientos-, se realizaron entrevistas a profesionales de la comunicación, especialistas en el área digital y fundadores de medios periodísticos, conociendo el modelo de negocio para mantener y rentabilizar sus empresas. Los resultados de esta investigación están presentados en tablas, ordenando las respuestas de las entrevistas, procediendo a interpretarlas, evidenciando mediante gráficos estadísticos, la información obtenida de cada medio digital, para seguidamente mostrar las conclusiones y recomendaciones del trabajo investigativo. Con esta investigación, se permitió establecer los medios digitales con mayor reconocimiento en la provincia de El Oro, los cuales fueron sometidos a un análisis minucioso, además se determinaron los factores que han permitido que se posicionan en el mercado orense.
Keywords: MODELO DE NEGOCIO; EMPRENDIMIENTO; MEDIO DIGITAL; PERIODISMO